ANALISIS MEKANISME KOMPENSASI PAJAK PERTAMBAHAN NILAI PADA PT. SAUDARA SUKSES SEJAHTERA - Kevin Adrian Maulana; Saipudin; M. Yasin (Universitas Lambung Mangkurat, 2025)
This study aims to analyze the implementation of the Value Added Tax (VAT) compensation mechanism at PT. Saudara Sukses Sejahtera. The research adopts an applied method, utilizing both qualitative and quantitative data. Empirical evidence was collected through direct observation, interviews with company personnel, and documentation review, including tax invoices and VAT Periodic Tax Returns from Juni to September 2024. The data analysis focused on the calculation procedures, reporting processes, and the alignment of the applied compensation method with existing tax regulations. The finding reveal that the company correctly executed the VAT compensation by reallocating the August overpayment to the September tax period, effectively reducing the tax burden in that month. Although the procedures followed were in compliance with current regulations, a technical limitation was identified the company still uses the e-Faktur system, while the Directorate General of Taxes has transitioned to the Coretax platform. This research offers platform. This research offers practical insights that may serve as a useful reference for other businesses seeking to implement VAT compensation mechanisms accurately and in accordance with applicable tax law